Comparative analysis activation of post-receptor signal ways by dimeric dipeptide mimetiks of different loops of NGF - T. A. Antipova; I. O. Logvinov; S. V. Nikolaev; S. V. Kruglov; A. V. Tarasiuk; P. I. Antipov; T. A. Gudasheva; S. B. Seredenin (LLC "Publisher OKI", 2016)
On culture of hippocampal HT-22 cells line it is shown that dimeric dipeptide mimetiks of different Loops of NGF realize their action via specific neurotrophic TrkA-receptor and selective activate post-receptor intracellular signal ways. Mimetiks of 1th (GK-6 (10-6M)) and the 3rd Loops (GTS-115 ((10-6M)) evoke activation of two main signal cascades - PI3/Akt and MAP/Erk, while mimetic the 4th loop of NGF (GK-2 (10-8M)) only one - a PI3/Akt-way.